2019
DOI: 10.1101/578567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SMAUG: Analyzing single-molecule tracks with nonparametric Bayesian statistics

Abstract: AbstractSingle-molecule fluorescence microscopy probes nanoscale, subcellular biology in real time. Existing methods for analyzing single-particle tracking data provide dynamical information, but can suffer from supervisory biases and high uncertainties. Here, we introduce a new approach to analyzing single-molecule trajectories: the Single-Molecule Analysis by U Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…More recently, nonparametric methods have been reported that uncover a range of possible diffusion states within a single particle track, independent of pre‐defined parameters. For example, the Single Molecule Analysis by Unsupervised Gibbs Sampling algorithm provides the number of mobility states, the fraction, and the average diffusion coefficient of each state, as well as the probability of transitioning between two states (Karslake et al, ). Alternatively, background fluctuations arising from out‐of‐focus fluorescence or diffusion in the Z ‐direction can be addressed by the newly developed Single‐Molecule Accurate LocaLization by LocAl Background Subtraction algorithm (Isaacoff, Li, Lee, & Biteen, ).…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…More recently, nonparametric methods have been reported that uncover a range of possible diffusion states within a single particle track, independent of pre‐defined parameters. For example, the Single Molecule Analysis by Unsupervised Gibbs Sampling algorithm provides the number of mobility states, the fraction, and the average diffusion coefficient of each state, as well as the probability of transitioning between two states (Karslake et al, ). Alternatively, background fluctuations arising from out‐of‐focus fluorescence or diffusion in the Z ‐direction can be addressed by the newly developed Single‐Molecule Accurate LocaLization by LocAl Background Subtraction algorithm (Isaacoff, Li, Lee, & Biteen, ).…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…Other packages with information theoretic frameworks for trajectory analysis have been released; for example, the Single-Molecule Analysis by Unsupervised Gibbs sampling ("SMAUG") software package [9] also uses Bayesian estimation to characterize diffusive environments. However, our package is unique because it is intended specifically to provide lightweight trajectory analysis and prediction that can be used by those with a biological background to inform microscopy experiment design, without requiring deep statistical or computational knowledge.…”
Section: Plos Onementioning
confidence: 99%
“…By mapping the diffusivity estimates from each trajectory (value most probable from posterior distribution) to the spatial region where the tracked substrate was localized, the user can build up a spatial mapping of the diffusivity. While frameworks exist for spatial mapping of the physical properties of cells, such as nanorheology of injected particles [15] and SMAUG [9], these techniques respectively require an extensive and invasive experimental design or in-depth knowledge of computational Bayesian inference. Our tool offers an approachable framework for experimental design of studies to probe the spatial variation of physical properties of the cell.…”
Section: Application To Spatially Dependent Diffusivity Characterizationmentioning
confidence: 99%
“…We benchmark this analysis method, with simulation of transitioning particles and implement modifications that account for specific experimental challenges, such as varying tracking windows and confinement effects within the cell. Furthermore, we compare anaDDA to a different kinetic analysis tools that use Bayesian statistics or unsupervised Gibbs sampling to infer state transitions from the data 27,28 . We study the effects of confinement and tracking parameters on the fitting of the distribution coefficient distribution and re-analyse previously published sptPALM data of DNA interacting proteins, obtain their kinetic parameters, and reveal that fast DNA probing interactions were hidden in the published data.…”
Section: Introductionmentioning
confidence: 99%